Naruszenia reguły zakonnej przez Krzyżaków i ich karanie w Prusach w pierwszej połowie XV w. - Duda, Michalina; Jóźwiak, Sławomir (Kwartalnik Prawa Publicznego, 2014)
Punishing proceedings stipulated for Teutonic Knights were contained primarily by the Laws drafted before the middle of the 13th century. Above-mentioned regulations distinguished four grades of crimes and punishments directly attributed to respective category of misdeeds. Consecutive acts, although largely repeating the initial regulations, introduced a number of new provisions related to punishing Teutonic Knights. Due to the few preserved sources, it is hard to comprehensively present how these regulations were precisely applied. In fact, very helpful are sources from the Teutonic Order State in Prussia from the first half of the 15th century. Unfortunately, mentions about crimes committed by Teutonic Knights rarely contain information related to carrying out the penalties. Nevertheless, it is worth noting that Teutonic Knights committed the offenses included in first, second and third category of misdeeds (there is lack of information about the most serious offenses – fourth category in the sources), were punished by the confiscation of the coat and imprisonment in the castle’s tower. Fundamentally, the confinement last from a few months to half a year and its length was not closely related to the type of offense . Laws entitled the grand masters to acquit the accused. Interestingly, the Teutonic Knights demanded from their superiors to narrow down the punishments to the confiscation of the coat and not to punish a brother-knights by putting them into irons or imprisoning in a tower in the middle of the 15th century However, it is not known whether this postulate were realized .